Mesalazine-induced myopericarditis in a patient with ulcerative colitis - Asadi, Jalal (Echo Res Pract, 2017)
A 25-year-old male with a background of ulcerative colitis presented with a two-week history of central chest pain. His ECG on presentation showed global T wave inversion with a peak troponin I of 165 ng/mL. Clinical diagnosis of myopericarditis/myocarditis was made. Echocardiography and cardiac magnetic resonance (MR) confirmed the diagnosis. On detailed assessment of his medication history, mesalazine was suspected as an etiological factor, with discontinuation resulting in an improvement in symptoms, inflammatory markers and cardiac enzymes. This is a unique case of mesalazine-induced myopericarditis on a background of inflammatory bowel disease. LEARNING POINTS: Myopericarditis can be due to infectious and non-infectious causes. Myopericarditis may be related to systemic diseases such as inflammatory bowel disease (IBD) or as a consequence of its treatment. Cardiac magnetic resonance has proven to be a valuable technique for assessing myocardial injury and inflammation in myocarditis. Importance of taking a thorough medical history to distinguish the type of chest pain in order to make a correct diagnosis.